ĐK: [TEX]log_3(log_4x) > 0 \Leftrightarrow x > 4[/TEX]
Đặt [TEX]t=log_4x > 1 \Rightarrow log_2x=2t[/TEX]
[TEX]PT \Leftrightarrow log_2(log_3t)=log_4(log_32t)= \frac{1}{2}log_2[log_3t+log_32][/TEX]
[TEX]\Leftrightarrow log^2_3t=log_3t+log_32[/TEX]
Đến đây giải tiếp được rồi
ĐK: x > 1
Đặt [TEX]t=log_2x \Rightarrow x=2^t[/TEX]
[TEX]PT \Leftrightarrow log_2(log_32^t)=log_3t \Leftrightarrow log_2(tlog_32)=log_3t[/TEX]
[TEX]\Leftrightarrow log_2t+log_2(log_32)=log_32.log_2t[/TEX]
Đến đây thì OK rồi
ĐK: x > 1
Đặt [TEX]t=log_2x \Rightarrow x=2^t[/TEX]
[TEX]PT \Leftrightarrow log_2(log_32^t)=log_3t \Leftrightarrow log_2(tlog_32)=log_3t[/TEX]
[TEX]\Leftrightarrow log_2t+log_2(log_32)=log_32.log_2t[/TEX]
Đến đây thì OK rồi